The influence of curriculum design on university students’ academic performance in Cambodia: Exploring the mediating role of self-regulation - Lork, Chumneanh; Ali, Dhakir Abbas (Edelweiss Applied Science and Technology, 2025)
This study investigates the influence of curriculum design on university students’ academic performance in Cambodian higher education, emphasizing the mediating role of self-regulation. A quantitative research design was adopted, collecting data from 320 lecturers across public and private universities. Using SmartPLS (PLS-SEM), the measurement model demonstrated strong reliability (Cronbach’s α > 0.90) and validity (AVE > 0.60). The structural model explained 15.6% of the variance in self-regulation and 11.8% in students’ performance, with Q² values above zero, confirming predictive relevance. Curriculum design did not significantly affect students’ performance directly (β = 0.099, t = 1.655, p = 0.099) but had a strong positive effect on self-regulation (β = 0.405, t = 8.580, p = 0.000). Self-regulation significantly enhanced students’ performance (β = 0.296, t = 5.420, p = 0.000) and mediated the relationship between curriculum design and students’ performance (β = 0.120, t = 4.370, p = 0.000). The results suggest that curriculum design indirectly improves academic outcomes by fostering self-regulatory skills. These findings highlight the need for learner-centered, goal-oriented curricula that actively cultivate self-regulation, empowering students to manage their learning processes and achieve better academic performance.